2003
DOI: 10.1097/01.ta.0000064449.11809.48
|View full text |Cite
|
Sign up to set email alerts
|

The Cushion Effect

Abstract: Although no difference in ISS was identified between the lean and obese cohorts, there was an increase in mortality with the obese cohort. The severity of lower extremity injuries increased with increasing BMI. The overweight cohort was associated with lower ISS and abdominal mAIS score compared with the lean cohort. This protection may be attributable to an increase in insulating tissue, or a "cushion effect," without a significant increase in mass and momentum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
183
3
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(197 citation statements)
references
References 16 publications
6
183
3
5
Order By: Relevance
“…9 In addition, we observed a positive relationship between BMI and injury-related expenditure, possibly because of an increased severity of injury and higher injury frequencies among those obese adults. 3,4 Earlier, a retrospective review study of 316 patients in a Los Angeles County Medical Center found that obese patients had more complications and required longer intensive care unit stays (obese 8±9 days vs non-obese 6±6 days, P ¼ 0.05) after severe trauma. 27 Despite the fact that our data were unable to identify injury severity and the number of times that the subject was injured, there is clear evidence that obesity has an impact and increases the risk of injury also increasing injury-related expenditure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In addition, we observed a positive relationship between BMI and injury-related expenditure, possibly because of an increased severity of injury and higher injury frequencies among those obese adults. 3,4 Earlier, a retrospective review study of 316 patients in a Los Angeles County Medical Center found that obese patients had more complications and required longer intensive care unit stays (obese 8±9 days vs non-obese 6±6 days, P ¼ 0.05) after severe trauma. 27 Despite the fact that our data were unable to identify injury severity and the number of times that the subject was injured, there is clear evidence that obesity has an impact and increases the risk of injury also increasing injury-related expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that obesity is associated with injuries, especially sport and motor vehicle injuries. [3][4][5] Some studies have identified an increased risk of injury among young overweight and obese groups of people. 6,7 Other research, from cross-sectional studies, has shown that increased body weight is associated with an increased risk of unintentional injury 8,9 and with workplace traumatic injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the uncontrolled nature of traumatic injury, the study of obesity is challenging in this orthopedic population. Fracture patterns can be different based on BMI, such that obese patients tend to sustain fewer head injuries, more lower extremity fractures 5 and more severe lower extremity injuries and rib fractures after trauma 37,38 compared to non-obese counterparts. Alternatively, the variation among studies may be due to injury heterogeneity of orthopedic trauma cohorts and functional status on discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly occupants are at increased risk of injury (Moran et al, 2002;Peterson et al, 1998). There are studies that indicate that high BMI's are associated with increased severity of lower extremity injury (Arbabi et al, 2003;Boulanger e al, 1992).…”
Section: Motor Vehicle Collisionmentioning
confidence: 99%